Representation of Karo Culture in the Early 20th Century in P. A. J Moojen’s Paintings - Ariani Ariani; Imam Santosa; Achmad Haldani Destiarmand; Agus Sachari (MOZAIK HUMANIORA, 2022)
cultural and artistic point of view with a cultural studies approach. The results of the study show that Moojen's paintings represented the belief systems, social stratification systems, and art systems of Karo culture in the early 20th century. In conclusion, Moojen's paintings are able to provide an overview of the reality of the life of the Karo people who lived in the early 20th century that cannot be separated from elements of traditional Karo buildings.Â